The role played by jesuit missionaries in signing the treaty of Nerchinsk in 1689 signed between Russia and China - Junquera Rubio, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
In 1689, Russia and China signed the Treaty of Nerchinsk. The reason came from colonization they were developing the Russians on the Amur River, especially in the major tributaries. The Cossacks had established some strog (fort) to establish contact with Aboriginal people and for charging the tax. The Russians originated many problems and exhausted diplomacy, Kangxi Emperor sent troops to attack the Russians and evict the Amur River. In the strog of Nerchinsk the two delegations met to sign peace and Jesuit missionaries played a prominent role during the negotiations role and were responsible for drafting the document in Latin, translated the Manchu and help its development in Russian.